The Demand of Affordable Housing Among Middle-Income Group (M40) in Negeri Sembilan - Sharulnizam, Muhammad Emirul Luqman (Research in Management of Technology and Business, 2022)
Demand for affordable housing is increasing especially in developing areas such as Seremban. Locational factors and many amenities have been a major factor in increasing the demand for affordable housing (RMM). As we can see, the RMM set up by both the government and the private sector is located far from the workplace and does not have sufficient initial facilities. Home buying can be measured by various factors such as physical factors and income for long term comfort. The purpose of this study was to identify factors that influence the demand for affordable housing among the middle-income group (M40) in Negeri Sembilan. The data used in this study were quantitative data by conducting research, surveys, virtual interview and analyzing the data with the Statistical Package for Social Sciences (SPSS) and Geographic Information System (GIS). Based on the data, the study can identify the decisive factor in buying a house in Negeri Sembilan is the price as it is in line with the income of most of the population (M40). In this study, affordable housing is greatly influenced by the macro and micro factors that are key factors in meeting the needs of the people in Negeri Sembilan. This study can also serve as a guide for developers to improve housing construction to further develop their housing scheme.